Constructs across a hierarchical, dimensional model of psychopathology show differential associations with social and general cognitive ability - Scott D. Blain; Jerillyn S. Kent; Timothy A. Allen; Carly A. Lasagna; Chloe A. Peyromaure de Bord; Aisha L. Udochi; Scott R. Sponheim; Colin G. DeYoung; Ivy F. Tso (PLoS ONE, 2025)
Many psychiatric disorders and associated psychopathology dimensions are related to social cognitive deficits and reduced general cognitive ability. The current study applied a hierarchical, dimensional approach to better understand associations among psychopathology, social cognition, and general cognitive ability. Data were collected from two samples (n = 653), including psychosis-spectrum patients, their first-degree relatives, and individuals from community sources. Participants completed dimensional psychopathology measures and social cognition tasks (e.g., emotion perception and mentalizing). Data were analyzed using bi-factor exploratory structural equation modeling. Detachment—a psychopathology dimension conceptually linked to social functioning—was associated with worse social cognition, independent of general cognitive ability. Eccentricity and Machiavellianism were associated with better social cognition and general cognitive ability. Findings—and the hierarchical, dimensional approach employed—will be useful in informing future research on and interventions for social dysfunction.